Design and Construction of Solar Panel Cleaner - Abubakar, Rabiu Ahmad (Engineering Science & Technology, 2025)
This study presents an experimental evaluation of a motorized cleaning system designed to enhance the efficiency of Photovoltaic (PV) solar panels by removing surface dust and contaminants. The system comprises a mechanical unit that traverses the panel’s length, driven by a coordinated arrangement of motors, gears, and belts. Its operation is controlled by a timing mechanism that ensures synchronized back-and-forth motion of a dry-cleaning brush. The primary objective is to assess the system’s effectiveness in improving panel output, energy efficiency, and operational reliability. Five experimental runs were conducted on a dust-covered solar panel under stable environmental conditions. Key performance indicators included cleaning duration, energy consumed by the system, and solar output before and after cleaning. Results show an average cleaning time of 60.4 seconds per cycle and an energy consumption of 2.1 Wh. The panel’s power output increased from an average of 180 W before cleaning to 200 W after cleaning, marking an approximate 11% efficiency gain. This improvement significantly exceeded the operational energy cost, confirming the system’s high energy efficiency. The gear- and belt-driven mechanism enabled consistent and uniform brush movement, ensuring effective cleaning while minimizing the risk of surface abrasion. Its dry-cleaning approach makes it particularly suitable for arid regions where water use is limited or impractical. The system demonstrated reliable and repeatable performance across all test runs. In conclusion, the motorized cleaning system offers a practical and energy-efficient solution for maintaining solar panel performance. It is cost-effective, autonomous, and well-suited for integration into larger PV installations. Further research is recommended to evaluate its long-term durability, adaptability to different panel configurations, and potential integration with smart monitoring and control technologies.